EFFECT OF PROVIDING HIGH PROTEIN MILK INTAKE ON INCREASING HB LEVELS IN THIRD-TRIMESTER OF PREGNANCY WITH ANEMIA - Wulandari, Endah S; Yuliatin, . (E-Jurnal Medika Udayana, 2024)
The high maternal mortality rate in Indonesia was still dominated by 3 main causes, one of which was bleeding caused by anemia. Anemia was related to a lack of protein. so, what could be done to overcome this problem was by giving iron tablets with the addition of protein intake to pregnant women. This study aimed to determine the effect of giving high-protein milk intake on increasing Hb levels in TM III pregnant women with anemia. The research design was a one-group pretest-posttest pre-experiment. The population in this study were all third-trimester pregnant women with anemia in the working area of the Gondanglegi Public Health Center, Malang Regency, totaling 50 people, with a sample of 33 people. The statistical test used in this study is the Wilcoxon Signed Rank Test. The results showed that the average Hb level before being given treatment was 10,1 gr/dl, and after being given treatment was 11,1 gr/dl. The results of the data analysis showed that there was an effect of giving high-protein milk intake on increasing Hb levels in TM III pregnant women with anemia in the Working Area of the Gondanglegi Public Health Center (p = 0,000). This study concludes that milk protein intake has a significant effect on increasing Hb levels in pregnant women. It is recommended for pregnant women who have anemia to pay attention to their nutritional intake, especially protein intake.